A design of ILC E-driven positron source. Issue 1 (1st January 2023) - Kuriki, M; Tajino, H; Konno, S; Liptak, Z; Takahashi, T; Fukuda, M; Omori, T; Seimiya, Y; Urakawa, J; Yokoya, K; Kashiwagi, S
Abstract: ILC is an electron-positron linear collider based on Superconducting linear accelerator. Linear collider is the only solution to realize high energy electron-positron collision beyond the limit of synchrotron radiation energy loss by ring colliders. Beam current of injector of linear colliders is much larger than that of ring colliders because the beam is not reusable. Providing an enough amount of particles, especially positron is a technical issue. In this article, we present a design of electron driven positron source for ILC. After optimizations, the system design is established with an enough technical margin, e.g. avoiding potential damage on the production target.